Spatial examination of social and environmental drivers of Middle East respiratory syndrome coronavirus (MERS-CoV) across Kenya - Lawrence, T.J.; Kangogo, G.K.; Fredman, A.; Deem, S.L.; Fèvre, Eric M.; Gluecks, Ilona; Brien, J.D.; Shacham E. (Springer, 2024)
Climate and agricultural land-use change has increased the likelihood of infectious disease emergence and transmissions, but these drivers are often examined separately as combined effects are ignored. Further, seldom are the influence of climate and agricultural land use on emerging infectious diseases examined in a spatially explicit way at regional scales. Our objective in this study was to spatially examine the climate, agriculture, and socio-demographic factors related to agro-pastoralism, and especially the combined effects of these variables that can influence the prevalence of Middle East respiratory syndrome coronavirus (MERS-CoV) in dromedary camels across northern Kenya. Our research questions focused on: (1) How MERS-CoV in dromedary camels has varied across geographic regions of northern Kenya, and (2) what climate, agriculture, and socio-demographic factors of agro-pastoralism were spatially related to the geographic variation of MERS-CoV cases in dromedary camels. To answer our questions, we analyzed the spatial distribution of historical cases based on serological evidence of MERS-CoV at the county level and applied spatial statistical analysis to examine the spatial relationships of the MERS-CoV cases between 2016 and 2018 to climate, agriculture, and socio-demographic factors of agro-pastoralism. Regional differences in MERS-CoV cases were spatially correlated with both social and environmental factors, and particularly ethno-religious camel practices, which highlight the complexity in the distribution of MERS-CoV in dromedary camels across Kenya.